Effects of relationship functioning on the biological experience of stress and physical health. (February 2017) - Farrell, Allison K; Simpson, Jeffry A
Highlights: Relationship functioning influences stress responses and health outcomes. Negative relationship functioning generally induces larger stress responses and worse health. Positive relationship functioning generally buffers stress and improves health. Future research should test mechanisms, moderators, and integrate developmental perspectives. Abstract : In this paper, we outline how relationship functioning affects the biological experience of stress and its consequences for physical health. Negative relationship perceptions and processes, such as attachment insecurity, hostility, and frequent conflict, tend to heighten stress responses and generate worse health over time, whereas positive relationship perceptions and processes, such as responsiveness, support, and intimacy, are generally associated with reduced or buffered stress responses and improved health (with some caveats). Future research should focus on the mechanisms behind these effects, the extent to which they can be changed or reversed, incorporating developmental perspectives, and effects of individual differences on these processes.